Oral Hygiene and Gingivitis Among Schizophrenic Patients at Karangkembang Regional General Hospital: A Cross-Sectional Study - Eva Mufida Ikhdati; Kusuma Astuti N. P; Agus Marjianto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Schizophrenia is a chronic mental disorder that can affect an individual's ability to maintain oral hygiene. This condition may lead to dental and oral health problems, such as gingivitis. An examination conducted in August 2024 on 30 patients with schizophrenia showed that 93% of them experienced gingivitis, indicating a high prevalence of gingivitis among patients with schizophrenia. This study aims to determine the relationship between oral hygiene and gingivitis in patients with schizophrenia at Karangkembang Regional Public Hospital, Lamongan Regency, in 2025. This research uses an analytical survey with a cross-sectional design involving 77 patients with schizophrenia. Data were collected through oral examinations to assess the patients’ oral hygiene and gingival condition. Data analysis was conducted using the Spearman rank correlation test to determine the relationship between oral hygiene and gingivitis in patients with schizophrenia, with a significance level (α) = 0.05. If the analysis result shows a ρ-value < 0.05, then H1 is accepted. If the ρ-value > 0.05, then H1 is rejected. The result of the Spearman rank test showed a ρ-value of 0.000. This value is smaller than the predetermined significance level (α = 0.05), thus H1 is accepted. This means there is a relationship between oral hygiene and gingivitis in patients with schizophrenia at Karangkembang Regional Public Hospital, Lamongan Regency, in 2025. The correlation coefficient (ρ) is 0.531, indicating a strong relationship between oral hygiene and gingivitis in patients with schizophrenia.